Consolidation process of uncemented backfill slurry in a mine stope considering hydro-geotechnical properties of rockmass in adjacent stopes - Guangsheng Liu; Qinghai Ma; Xiaocong Yang; Lijie Guo; Li Li (Scientific Reports)
Abstract In open stoping with subsequent backfill mining, the filled slurry in one stope is typically surrounded by the rockmass in adjacent stopes. The rockmass generally contain geological faults and joints that can serve as seepage pathways for pore water within the backfill slurry during consolidation process. However, these impacts from the adjacent rockmass were usually simplified to an impermeable or permeable boundary in previous studies. In this paper, numerical modeling with FLAC3D was conducted to investigate the influences of hydro-geotechnical properties of surrounding rockmass on consolidation process of uncemented backfill slurry in a vertical stope. Results show that the pore water pressure (PWP) and effective stresses of backfill slurry confined by rockmass are consistently higher than those obtained by assuming fully permeable boundaries but lower than those derived from impermeable boundary assumptions. A five-fold difference in peak PWP and effective stresses occurs when the rockmass hydraulic conductivity varies from 10–8 m/s to 10–5 m/s. It is reasonable to simplify the rockmass with a low hydraulic conductivity (≤ 10–8 m/s) as an impermeable boundary and that with high hydraulic conductivity (≥ 10–5 m/s) as a permeable boundary. Additionally, a higher porosity and lower initial saturation of the adjacent rockmass promote both PWP dissipation and effective stresses development in backfill slurry, but their influences are less pronounced compared to the effect of hydraulic conductivity. Furthermore, the study discusses the influences of the hydro-geotechnical properties of adjacent rockmass on the lateral earth pressure coefficient of consolidated backfill which is an important parameter for analytical models of stress distribution within backfill. The findings are expected to provide valuable insights into the consolidation behavior of backfill slurry under field conditions and contribute reliable method for barricade design.